(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Surface engineering of Al alloys by deposition of hydrophobic coatings using different techniques to improve the wear and corrosion resistance and self-cleaning properties has gained more attention in the last years. This study is an attempt to use thassos additives in modification of the electrolytes used in the micro-arc oxidation MAO process for the deposition of hard and super hydrophobic Al2O3 ceramic coatings on Al alloys for heavy load-bearing tribological and self-cleaning applications. Thassos rocks in different concentrations (1, 2, 3, 5 and 7 g/L) were used as modification components. Ceramic coatings of Al2O3 were deposited on Al alloy by using a homemade MAO unit with an applied voltage of (320-350) V, current of (0.1-0.3) A and a temperature of (15-25°C), and at different deposition times (10-45min). The coated surfaces were post-treated using fatty acids such as myristic acid (10g/L) and stearic acid (5g/L) for important self–cleaning properties. Various analytical techniques and tests were used to characterize the coatings such as scanning electron microscopy (SEM), X-ray diffraction (XRD), hardness, thickness, and angle of contact measurements and tests. The highest contact angle of 95.120° was achieved when using thassos (3g). This high contact angle indicates that the surfaces are highly hydrophobic, which means that they repel water effectively. The best result for the highest hardness value recorded was 975.9 HV when using thassos (7g) as additives. Results from this research will promote future works in surface engineering of Al alloys by MAO process using more environmentally friendly, readily available and require minimal process additions such as ceramic natural additions of thassos in the deposition of hard and hydrophobic ceramic coatings for wear resistance and self-cleaning applications.